Exploring English Students’ Perception of Lecturer’s Corrective Feedback in Writing Class - Putri, Widia Amara; Lestari, Iin Widya; Wafa, Khoirul (Universitas Sulawesi Barat, 2024)
Corrective feedback plays a crucial role in the teaching and learning process, particularly in developing students' writing skills. This research explores English language students' perceptions of lecturers' corrective feedback in writing classes and its impact on their writing motivation. Employing a qualitative descriptive approach, data were collected through questionnaires and interviews from 15 participants. The findings reveal that students have a positive perception of the corrective feedback provided by lecturers during writing classes. They perceive the feedback as beneficial in enhancing their understanding of writing tasks and identifying areas for improvement. Notably, only 27% of students acknowledged experiencing negative emotions such as sadness, confusion, or disappointment when unable to comprehend the lecturers' feedback. Overall, students greatly appreciate the oral and written corrective feedback, as it substantially aids in developing their writing proficiency. Furthermore, the study highlights the positive impact of lecturers' feedback on students' motivation in writing, fostering enthusiasm, focus, and a willingness to learn. These findings underscore the importance of effective corrective feedback strategies in enhancing students' writing skills and sustaining their motivation in the learning process.